2015
DOI: 10.1093/jnci/dju423
|View full text |Cite
|
Sign up to set email alerts
|

Informed Cytology for Triaging HPV-Positive Women: Substudy Nested in the NTCC Randomized Controlled Trial

Abstract: Background:Human papillomavirus (HPV)–based screening needs triage. In most randomized controlled trials (RCTs) on HPV testing with cytological triage, cytology interpretation has been blind to HPV status.Methods:Women age 25 to 60 years enrolled in the New Technology in Cervical Cancer (NTCC) RCT comparing HPV testing with cytology were referred to colposcopy if HPV positive and, if no cervical intraepithelial neoplasia (CIN) was detected, followed up until HPV negativity. Cytological slides taken at the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 25 publications
1
57
2
4
Order By: Relevance
“…This more objective nature might also be of value, in particular in the triage of high-risk HPV-positive women, in which prior knowledge of high-risk HPV presence could result in a scoring 'bias' that likely will decrease specificity of Pap cytology, 32,33 as was also observed in the present study. Yet, it should be realized that p16/Ki-67 dual-stained cytology remains microscopy-based, in contrast to other suggested molecular triage tests.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This more objective nature might also be of value, in particular in the triage of high-risk HPV-positive women, in which prior knowledge of high-risk HPV presence could result in a scoring 'bias' that likely will decrease specificity of Pap cytology, 32,33 as was also observed in the present study. Yet, it should be realized that p16/Ki-67 dual-stained cytology remains microscopy-based, in contrast to other suggested molecular triage tests.…”
Section: Discussionmentioning
confidence: 59%
“…Besides the use of an outpatient population, the prior knowledge of high-risk HPV presence to the cytotechnicians and cytopathologists might be an explanation for the high sensitivity of cytology in the current study. 32,33 By adjusting the threshold of abnormal cytology from ≥ ASC-US to ≥ LSIL in our study, sensitivity would decrease from 87.7 to 77.8%, with a corresponding increase in specificity from 44.9 to 72.3%. A similar finding was recently described by Ebisch et al (in press).…”
Section: Discussionmentioning
confidence: 78%
“…However, cytology comes with some limitations, including its subjective nature and the required repeated cytology to ensure sufficient safety in the screening program. Moreover, prior knowledge of hrHPV-positivity influences cytology reading, which may result in an increase of false-positive referrals with simultaneously higher costs for the healthcare system [4749]. Recent clinical validation studies in screening populations have shown that DNA methylation markers provide a good alternative for cytology [14,5054].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, these estimates were obtained in study settings where cytologists were blinded to hrHPV-test results. Recently, it has been shown that providing cytologists with information on the hrHPV-positive status of participants increases the overall sensitivity of Pap cytology [48,49], probably due to the beneficial preselection of a population with a higher a priori cervical cancer risk. This is, however, at the cost of a significant decrease in specificity, which can be seen as the negative consequence of a more meticulous cytological evaluation [49,50].…”
Section: Pap Cytologymentioning
confidence: 99%